Oxygen Therapy Against Changes in Oxygen Saturation Levels in Patients with Head Injuries - Abdul Herman Syah Thalib; Nur Ain Madji (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: The impact on head injury is trauma to the scalp, brain, and skull, so to maintain stable oxygenation in body and brain tissues, oxygen therapy is very important in head injury patients so that oxygen saturation levels increase. Objective: To determine the description of oxygen therapy on changes in oxygen saturation levels in clients with head injuries. Methods: descriptive case study with the subjects used were 2 patients through inclusion and exclusion criteria. Results: Results: Changes in oxygen saturation levels in patients Head injuries A and H for 3 days experienced an increase after receiving oxygen therapy of 3 L/minute through a nasal cannula. Conclusion: nasal cannula oxygen therapy can increase oxygen saturation.